Transfusion treatment impact in the improvement of haematological parameters in patients with gastrointestinal bleeding - Iliriane Bunjaku; Mimoza Zhubi; Bukurije Zhubi; Emrush Kryeziu; Sadik Zeka (Journal of Health Sciences, 2012)
Introduction: Transfusion treatment (TT) is necessary in patients with gastrointestinal bleeding (GIB) for lost blood substitution. This study was aimed at assessing the changes in haematological parameters  (hemoglobin, hematocrit, red blood cell count, white cell count, platelet count and prothrombin time) before and after TT in anaemic patients with GIB in order to analyse the effect of this treatment. Methods: There have been included 293 patients with GIB (the average age was 57.3, ranged from 18-89 years) who were treated with TT at the Internal Clinic at the University Clinical Center Prishtina during one year period. Data for applied blood product and results of the coagulation screen (PT) were collected from the Kosovo’s Blood Transfusion Center (KBTC). Results: TT has been carried out in 404 episodes, with 714 units of concentrated red blood cells (78.6%), 189 units of fresh frozen plasma (20.8%) and concentrated platelets (0.6%), with an average dose 3.1 for transfunded patients. Average values of Hb before and after TT were 71.8 g/L and 81.4 g/L, respectively; while the average values of hematocrite before and after TT were 22.9% and 25.6%, respectively. The average erythrocytes count before TT was 2.6 respectively after treatment 2.8(p<0.0001). The PT was carried out in the 43% of patients with GIB before treatment with FFP, but after that only in 2% of cases. Conclusions: Having in mind difficult clinical and unsustainable situation in patients with gastrointestinal bleeding, the Transfusion Treatment resulted in the considerable improvement of the specific blood indicators.